Effects of Acute Stretching on Cognitive Function and Mood States of Physically Inactive Young Adults. Issue 1 (February 2020) - Sudo, Mizuki; Ando, Soichi
Exercise intensity from stretching is very low, making it well suited to varied populations, including physically inactive people. We tested the hypothesis that acute stretching would improve cognitive function and improved mood states in physically inactive people. We asked 19 physically inactive young participants to perform the Stroop task and complete the short form of Profile of Moods Scale before and after 10 minutes of whole body stretching using yoga techniques and poses (stretching condition) versus a resting period. In the stretching condition, we observed decreases in Tension–Anxiety, Depression–Dejection, Anger–Hostility, Fatigue, and Confusion scores on the Profile of Moods Scale (all p values < .01) and an increase in the Vigor score ( p = .01). We also observed a decrease in Stroop interference performance ( p < .001). Furthermore, we found a significant negative correlation between ΔVigor score and ΔStroop interference ( r = −.36, p = .03), indicating that a greater increase in the Vigor score was associated with better cognitive performance. Thus, acute stretching improved mood states and cognitive performance in physically inactive people. We suggest that the improved cognitive performance may be, at least partly, associated with the improved mood states.